Analytic optimization of Joule–Brayton cycle-based pumped thermal electricity storage system. (March 2022) - Wang, Liang; Lin, Xipeng; Zhang, Han; Peng, Long; Zhang, Xinjing; Chen, Haisheng
Highlights: Analytic optimization approach for Joule–Brayton PTES based on exergy theory was proposed. Analytic optimization is conducted for charge, storage and delivery processes individually. Theoretical equations considering various losses are provided. RT efficiency of 81.2%, 85.6%, and 88.2% achieved at 900 K, 1100 K, and 1300 K, respectively. In-depth perspective of a balance between RT efficiency and energy storage density is provided. Abstract: Having the advantages of high efficiency and high energy storage density, pumped thermal electricity storage (PTES) is a promising mechanical energy storage technology that is typically suitable for large-scale energy storage. To obtain the combined influence of various factors and losses on the performance of a PTES system, an analytic optimization study for the individual process of charge, storage, and discharge are conducted in this study. The results indicate that the maximum working temperature and the efficiency of the turbomachines are positively correlated to the round-trip efficiency and the energy storage density. Moreover, the optimal pressure ratio needs to be determined to maintain the balance between the efficiency and the energy storage density. The Joule–Brayton PTES system can achieve maximum round-trip efficiencies of 81.2%, 85.6%, and 88.2% at 900 K, 1100 K, and 1300 K, respectively, under a turbomachine efficiency of 0.9. With reasonable temperature and pressure losses (not optimal components), a round-trip efficiency of 59% and an energy storage density of 60 kWh/m 3 can be obtained at the maximum temperature of 1100 K. The above analysis and optimization based on the exergy method provide a theoretical approach for the future design of a Joule–Brayton cycle-based PTES system. Graphical abstract: Image, graphical abstract